Religious transformation as a psychological process: A review of Islamic psychology of religious practices in Indonesia in literature review - Pramudyawardhani, Aisyiah Galuh; Salsabil, Alya Zakiah; Flavia, Mona (Arshaka: Social Sciences and Education, 2025)
The phenomenon of religious transformation in Indonesia has become increasingly evident in both personal and communal aspects of society. However, in-depth research on the practice of religious transformation in Indonesia remains limited. This article aims to examine various forms of religious transformation practices within the framework of Islamic psychology through a narrative literature review approach. The method employed is a narrative literature review using the SPIDER framework (Sample, Phenomenon of Interest, Design, Evaluation, and Research Type) to identify and analyze various religious transformation practices found in existing Indonesian studies. The findings reveal that religious transformation in Indonesia is not a singular or uniform process but manifests in a variety of religious practices. Activities such as dhikr, prayer, Qur’anic recitation, listening to religious lectures, attending study circles (pengajian), and other devotional acts can strengthen spirituality, shape religious identity, and encourage more positive behavioral changes. The Islamic psychological perspective highlights that religious transformation is not merely a sociological or cultural symptom but rather a complex inner journey toward closeness to Allah.